Sasaran Pendidikan dalam al-Qur’an - Alfiyah, Avif; Rahman, Mustahiqur; Omy Husnusyifa, Daeng (Darajat: Jurnal Pendidikan Agama Islam, 2022)
This article is discuss paragraph in al-Quran about objek of education in surah al-Syu’ara’ 214 and surah al-Tahrim 6. That is focus in three of tafsir book. That is Tafsir al-Misbah Quraish Shihab, tafsif al-Azhar Buya Hamka, and tafsir Fi Dzilalil Qur’an Sayyid Quthb. The urgent of this article is knowing argument from three of tafsir book about objek of education. We must understand difference tafsir from whom with each argument and analysis specif`ic. This article using tafsir muqaran in order to get understand dan knowing about that surah.